2021
DOI: 10.1016/j.apcatb.2021.119955
|View full text |Cite
|
Sign up to set email alerts
|

La1-x(Sr, Na, K)xMnO3 perovskites for HCHO oxidation: The role of oxygen species on the catalytic mechanism

Abstract: perovskites for HCHO oxidation: the role of oxygen species on the catalytic mechanism, Applied Catalysis B:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(17 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…It infers a higher reducibility of these species when more Co elements are added to the structure of the perovskite . It is generally known that the initial H 2 consumption rate can be applied to evaluate the low-temperature reducibility in Figure b . The greater the Co dopant, the higher the initial H 2 consumption rate, suggesting that the partial substitution of Ti 4+ cations by Co 3+ or Co 2+ enhances the low-temperature reducibility of SrTiO 3 -based catalysts.…”
Section: Results and Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…It infers a higher reducibility of these species when more Co elements are added to the structure of the perovskite . It is generally known that the initial H 2 consumption rate can be applied to evaluate the low-temperature reducibility in Figure b . The greater the Co dopant, the higher the initial H 2 consumption rate, suggesting that the partial substitution of Ti 4+ cations by Co 3+ or Co 2+ enhances the low-temperature reducibility of SrTiO 3 -based catalysts.…”
Section: Results and Discussionmentioning
confidence: 94%
“…15 It is generally known that the initial H 2 consumption rate can be applied to evaluate the lowtemperature reducibility in Figure 4b. 46 The greater the Co dopant, the higher the initial H 2 consumption rate, suggesting that the partial substitution of Ti 4+ cations by Co 3+ The behavior of active oxygen is also responsible for the catalytic combustion performance. 47 O 2 -TPD is employed to feature the oxygen species characteristics of flame-made perovskites.…”
Section: Morphology and Element Distributionmentioning
confidence: 99%
“…The surface lattice oxygen species of δ-MnO 2 was recently confirmed not to participate in ambient-temperature HCHO oxidation because the HCHO adsorption energy on surface lattice sites was too low to support HCHO oxidation. , Hence, the surface chemisorbed oxygen species and OH groups could oxidize HCHO into intermediate species (e.g., DOM, formate, carbonate). The consumed ROS could be continuously replenished by molecular O 2 or water vapor. , Recently, ROS generated from Fenton-like O 2 activation over Fe-MOF catalysts, including superoxide radicals ( • O 2 – ), hydroxyl radicals ( • OH), and singlet oxygen ( 1 O 2 ), were confirmed as active for HCHO oxidation . However, the specific role and contribution of the oxygen-free radical species in HCHO oxidation over Mn-based catalysts are still unidentified. Although the role of ROS in HCHO oxidation is under debate, the performance of catalysts can be promoted by increasing the amount of ROS via the introduction of surface oxygen vacancies.…”
Section: Introductionmentioning
confidence: 99%
“…The consumed ROS could be continuously replenished by molecular O 2 or water vapor. 18,19 Recently, ROS generated from Fenton-like O 2 activation over Fe-MOF catalysts, including superoxide radicals ( • O 2 − ), hydroxyl radicals ( • OH), and singlet oxygen ( 1 O 2 ), were confirmed as active for HCHO oxidation. 20 However, the specific role and contribution of the oxygen-free radical species in HCHO oxidation over Mn-based catalysts are still unidentified.…”
Section: Introductionmentioning
confidence: 99%
“…As for the catalysts of anodic oxidation reaction, the La–Mn perovskites were found to exhibit good oxidation characteristics . The experimental investigation indicated that A-site or B-site metal-doped perovskites can increase the catalytic efficiency . Therefore, it is safe to believe that metal-doped La–Mn perovskites are excellent catalysts for converting CH 3 OH to HCOOH.…”
Section: Introductionmentioning
confidence: 99%